Tackling the volatility paradox: spillover persistence and systemic risk - Christian Kubitza (European Central Bank (ECB), 2024)
Financial losses can have persistent effects on the financial sy stem. This paper proposes an empirical measure for the duration of these effects, S pillover P ersistence. I d ocument that Spillover Persistence is strongly correlated with financial c onditions; d uring b anking crises, Spillover Persistence is higher, whereas in the run-up phase of stock market bubbles it is lower. Lower Spillover Persistence also associates with a more fragile system, e.g., a higher probability of future crises, consistent with the volatility paradox. The results emphasize the dynamics of loss spillovers as an important dimension of systemic risk and financial constraints as a key determinant of persistence.
Keywords: E44; G01; G12; G20; G32; 330; Systemic Risk; Fragility; Financial Crises; Asset Price Bubbles; Fire Sales